2022
DOI: 10.1371/journal.pone.0263835
|View full text |Cite
|
Sign up to set email alerts
|

A comparative driving safety study of mountainous expressway individual tunnel and tunnel group based on eye gaze behavior

Abstract: The traffic environment of a tunnel group is more complex than that of a single tunnel, which increases the driving risk. The eye gaze behavior of drivers can be used to evaluate driving safety and comfort. To analyze the fixation characteristics of drivers in a single tunnel and tunnel group of mountainous expressways, an actual vehicle test is conducted. The test area has a total length of 160 km and 38 tunnels, including 8 tunnel groups and 16 single tunnels. In the test, the difference in the gaze time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Figure 8 shows the impact of vehicle speed and position on MTPA during the process of driving out of a long tunnel. It can be seen that the variation range of the MTPA value is (15)(16)(17)(18)(19)(20) in stage 3, suddenly increases to (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in stage 4, and decreases to (5-15) in stage 5. Comparing the height of the MTPA in the three sub-graphs, it can be found that the MTPA value has experienced a significant increase from stage 3 to stage 4, and then a drastic decrease from stage 4 to stage 5 when the vehicle leaves the long tunnel.…”
Section: E Effect Of Speed and Position On Mtpamentioning
confidence: 96%
See 1 more Smart Citation
“…Figure 8 shows the impact of vehicle speed and position on MTPA during the process of driving out of a long tunnel. It can be seen that the variation range of the MTPA value is (15)(16)(17)(18)(19)(20) in stage 3, suddenly increases to (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in stage 4, and decreases to (5-15) in stage 5. Comparing the height of the MTPA in the three sub-graphs, it can be found that the MTPA value has experienced a significant increase from stage 3 to stage 4, and then a drastic decrease from stage 4 to stage 5 when the vehicle leaves the long tunnel.…”
Section: E Effect Of Speed and Position On Mtpamentioning
confidence: 96%
“…Shang compared the drivers' eye gaze behavior in the tunnel group with the single tunnel based on the Markov chain and, the result showed that the design and management of tunnel groups were more complex than that of a single tunnel. e longer the tunnel, the greater the difference [28,29].…”
Section: Driving Safety Of the Tunnel Based On The Driver's Visualmentioning
confidence: 99%
“…Shang [27] divided the vision of a driver into five areas: inside the cab, near-distance road section in front of the vehicle, far-distance road section in front of the vehicle, rearview mirrors (left, right, and inside the vehicle), and other areas (such as the vault and side wall). As the viewing distance of the road in front of the vehicle includes both far and near distances, which cannot be quantified, this study combined them into one area (Area 1).…”
Section: Gazing Areamentioning
confidence: 99%
“…The interactions between tunnels increase the driving risks. Research on tunnel group design and operational management is needed [16].…”
Section: Introductionmentioning
confidence: 99%
“…[28,29]. Shang et al found the eye-gaze behavior of drivers can be used to evaluate driving safety and comfort in tunnel groups [16]. Xu et al reported that drivers were most significantly affected within the range between 250 m before the tunnel entrance and 50 m before the tunnel exit by collecting electrocardiogram (ECG) and eye movement data from 25 drivers during simulated driving [30].…”
Section: Introductionmentioning
confidence: 99%